Analysis and Prediction of Water Balance Using Dynamic Modelling to Solve Water Scarcity in Cimahi - Muhamad Fikri Fadhilah; Yayat Hidayat; Anne Hadiyane (3BIO: Journal of Biological Science, Technology and Management, 2022)
Cimahi is one of the most populated, fast-growing cities in Indonesia. Consequently, various environmental problems appear, primarily related to the sustainability of water resources. Exploitation and pollution of water, especially groundwater, are not accompanied by a good water conservation system that ensures proper water infiltration into the soil, causing several locations in the city to experience water deficits. The city may suffer a severe water shortage if this problem is unsolved. This study aims to predict and analyze the need and availability of water in Cimahi in the next few years to determine the right solution to deal with this problem. Analysis and prediction of water availability/needs were carried out by building a dynamic model using STELLA software for simulating the conditions in the next ten years. The results of the model were combined with the applicable spatial policies to formulate possible solutions. Results showed that Cimahi will experience a water crisis starting from 2029 with a total water deficit of 8.22 million M³. The model also predicted South Cimahi District is the area with the worst conditions where the water crisis has occurred since 2022 and peaked in 2029 with water sufficiency of only 59.83%. Based on local spatial planning laws and policies, the city's government is advised to improve its catchment area to protect its water resources. The vegetation cover area surrounding the catchment area can be improved, and water absorption capacity can be increased through civil technical actions such as building absorption wells. The model results showed that a proper solution could be done by expanding 142.8 Ha of green/vegetation cover, building 1576 units of absorption wells, and increasing the PDAM supply by 100 l/second.